Facilitators and Barriers of Sleep in Young Adults with Type 1 Diabetes - Griggs, Stephanie (Diabetes Educ, 2020)
PURPOSE: The purpose of this study was to explore the perceived facilitators and barriers for obtaining sufficient sleep in young adults with T1D. METHODS: A qualitative descriptive approach was used to generate data. In-depth semi-structured interviews with 30 young adults with T1D (66.7% female, mean age 22.1 years) were conducted. Interviews were transcribed verbatim and coded using NVivo™. RESULTS: Young adults with T1D reported feeling challenged at bedtime and overnight by the demands of a complex disease management regimen. General and diabetes-specific barriers and facilitators to obtaining sufficient sleep were the over-arching themes in the present study. Young adults perceived that electronic device use was a facilitator for relaxation before bed and a barrier to sleep by some participants. Delays in bedtime or disruptions in sleep were common diabetes-specific barriers. CONCLUSIONS: When designing sleep-promoting interventions for young adults with T1D, researchers should consider diabetes-specific challenges and solutions in addition to those present in the general young adult population.